RFX6 Regulates Insulin Secretion by Modulating Ca2+ Homeostasis in Human β Cells - Chandra, V; Albagli-Curiel, O; Hastoy, B; Piccand, J; Randriamampita, C; Vaillant, E; Cavé, H; Busiah, K; Froguel, P; Vaxillaire, M; Rorsman, P; Polak, M; et al. (Elsevier, 2014)
Development and function of pancreatic β cells involve the regulated activity of specific transcription factors. RFX6 is a transcription factor essential for mouse β cell differentiation that is mutated in monogenic forms of neonatal diabetes. However, the expression and functional roles of RFX6 in human β cells, especially in pathophysiological conditions, are poorly explored. We demonstrate the presence of RFX6 in adult human pancreatic endocrine cells. Using the recently developed human β cell line EndoC-βH2, we show that RFX6 regulates insulin gene transcription, insulin content, and secretion. Knockdown of RFX6 causes downregulation of Ca2+-channel genes resulting in the reduction in L-type Ca2+-channel activity that leads to suppression of depolarization-evoked insulin exocytosis. We also describe a previously unreported homozygous missense RFX6 mutation (p.V506G) that is associated with neonatal diabetes, which lacks the capacity to activate the insulin promoter and to increase Ca2+-channel expression. Our data therefore provide insights for understanding certain forms of neonatal diabetes.